2022
DOI: 10.3389/fmars.2022.987368
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of hypoxia and coupled physical-biogeochemical controls off the Changjiang (Yangtze River) Estuary in summer

Abstract: Global estuarine hypoxia is among the most acute environmental issues, yet the recognition of hypoxia variability remains patchy. The Changjiang (Yangtze River) Estuary (CE) is well known as one of the largest estuarine hypoxic systems. However, the mechanisms controlling the spatial variability and heterogeneity of summer hypoxia have been rarely examined in this region. Based on observational data in the summer of 2013, the essential linkages between physical-biogeochemical processes and spatial variability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 105 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…Based on the non-carbonate fraction, accumulation rates in the Cuchía succession can be attributed to mostly terrigenous input as indicated by Si which is of terrestrial origin because it correlates strongly with Al (r = 0.95) as observed in modern analog environments (Wei et al, 2022). In-situ production of carbonate by biomineralizers varies intermittently, such effects can be observed in many instances such as the TIC curve (Figure 3B), the variation of the major element Al (Figure 4C), and the TAR (Figure 7C).…”
Section: Role Of Terrigenous Input In the Accumulation Rate And Absen...mentioning
confidence: 95%
“…Based on the non-carbonate fraction, accumulation rates in the Cuchía succession can be attributed to mostly terrigenous input as indicated by Si which is of terrestrial origin because it correlates strongly with Al (r = 0.95) as observed in modern analog environments (Wei et al, 2022). In-situ production of carbonate by biomineralizers varies intermittently, such effects can be observed in many instances such as the TIC curve (Figure 3B), the variation of the major element Al (Figure 4C), and the TAR (Figure 7C).…”
Section: Role Of Terrigenous Input In the Accumulation Rate And Absen...mentioning
confidence: 95%
“…Furthermore, a temporal and spatial mismatch or decoupling of surface high-biomass regions and hypoxic zones was also observed. Nonuniform offshore advection and detachment of subsurface segments of water underlying the Changjiang River plume are the key drivers (Zhou et al, 2020;Wei et al, 2022). Zhang et al (2022) characterized the use of timescales of deficit and residence to evaluate near-bottom DO variations.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Wei et al (2021b) reported the mid-layer hypoxic phenomenon in the Zhejiang coastal area in August 2018 and attributed it to the seaward expansion of low-oxygen water protruding from the bottom-sloping region. As hypoxia expands off the CJE (Chen et al, 2020;Wang et al, 2021), the vertical structure of oxygen and nutrients becomes increasingly important (Wei et al, 2022). The pelagic organisms are more sensitive to oxygen than the benthos, thus the mid-layer hypoxia would be disastrous for their survival, especially for small zooplankton and juvenile fishes (Vaquer-Sunyer and Duarte, 2008;Hofmann et al, 2011).…”
Section: Introductionmentioning
confidence: 99%